AUTOMATION OF PRODUCTION OF FOAM BLOCKS AND GYPSUM BLOCKS. (Ustozlar uchun, 2024)
Abstract. Foam cinder blocks have revolutionized the construction industry, offering a lightweight and versatile alternative to traditional building materials. These innovative blocks combine the strength of concrete with the insulating properties of foam, making them an ideal choice for various construction projects. Their unique composition allows for improved energy efficiency, reduced construction time, and enhanced structural integrity.